Academic Procrastination in Virtual Classrooms: An Examination among Pre-Service Language Teachers during the Pandemic - Helengrace A. Lao; Kent Adnil C. Lao; Katreena Gayle A. Lao (International Journal on Integrated Education, 2022)
It goes without saying that the current global health crisis has managed to bring immense changes in our way of living, and one of the prominent changes it caused is manifested in the shift from face-to-face schooling to a virtual learning environment. Considering that distance education is now heavily inclined to performance assessment because of the external validity issues of online exams, an increase inthe amount of workload is expected. This in turn is conjectured to create more opportunities for students to practice Academic Procrastination (AP). Despite the rich repertoire of AP literature, it was observed that the vast majority of these studies were conducted prior to the pandemic and that the number of studies that relate to examining AP specifically amongpre-service language teachers amidst the pandemic isstill limited. This quantitative descriptive study conducted among 92 prospective language teachers aims to provideinsights on the degree of procrastination of pre-service language teachers studying under a virtual learning setting amidst a pandemic. Moreover, it also intends to examine the relationship between the respondents’ degree of procrastination in terms of their sex and their year level. The results revealed that in terms of the degree of AP indicators, the respondents displayed signs of being neutral academic procrastinators. As for their degree of procrastination tendencies, the respondents were found to manifest a low tendency to procrastinate on tasks. Moreover, the study also aimed to probe the respondents’ level of active procrastination to which resulted in the discovery that they possess neutral levels of active procrastination. Finally, in terms of the respondents’ degree of procrastination across the different areas of academic functioning, the results disclosed that the respondents have a somewhat high tendency to procrastinate on tasks in any area of academic function, and that their procrastination on these areas also has a somewhat high tendency of becoming a problem. Furthermore, it was found out that there is no significant difference between the respondents’ level of AP with both their sex and year level.